Effect of 5-membered bicyclic hydrocarbon additives on nanostructural disorder and oxidative reactivity of diffusion flame-generated diesel soot. (1st September 2020) - Abdrabou, Moataz K.; Morajkar, Pranay P.; Guerrero Peña, Gerardo D.J.; Raj, Abhijeet; Elkadi, Mirella; Salkar, Akshay V.
Abstract: Soot emission from diesel engines is of serious concern, as it is carcinogenic and remains suspended in air for a long time to cause adverse effects on human health and the environment. A way to reduce soot emission is by altering soot nanostructures by introducing fringe curvatures to enhance reactivity and increase oxidation. Such disorder in soot nanostructure can be initiated by the introduction of 5-membered rings into 6-membered, graphite-like soot structures. This study investigates the effect of the addition of norbornane, a saturated, 5-membered bicyclic hydrocarbon additive to diesel on the physicochemical properties, sooting propensity, structural disorders, and the oxidative reactivity of soot. The physicochemical analysis revealed that the threshold sooting index (TSI) of the blend is reduced to 29.5 at an optimum blending percentage of 10% norbornane-90% Diesel (NBD) as compared to the TSI of 37 for diesel. The analyses using XRD, Raman, HRTEM, and EDX indicated that the addition of this additive resulted in an increased soot nanostructural disorder, smaller PAH size, increased fringe curvature, and significantly greater aliphatic content in soot as compared to an unsaturated 5-membered bicyclic additive, dicyclopentadiene (DCPD). The reactivity studies confirmed that NBD soot is easily oxidized in air, since it requires a lower initial activation energy (90 kJ/mol) as compared to DCPD (120 kJ/mol) and pure diesel soots (170 kJ/mol). Thus, norbornane, a saturated 5-membered bicyclic compound, which is available as a by-product of polymer industry and in crude oil, can serve as a potential fuel additive for designing advanced fuels.